The Islamic Fundamentalism Based on Karen Armstrong's Perspective and Its Implications for The Identification of Fundamentalism Groups in Indonesia - Neli Rahmah; Nelmaya Nelmaya (Islam Realitas: Journal of Islamic and Social Studies, 2019)
One of the developments at the end of the twentieth century was the emergence of a militant piety popularly called "fundamentalism" in each religious tradition. This term was also used to indicate a new movement in the Islamic revival. Karen Armstrong stated three characteristics of the fundamentalism movement, including Islamic fundamentalism. First, the movements of ideology and theology came of the fear. Second, these movements were not old things, but they were modern, innovative and modernizing movements. Third, the fundamentalism groups had a textual understanding of religion. Armstrong's perspective on Islamic fundamentalism had implications for the Islamic Defenders Front (FPI) and the Indonesian Mujahidin Council (MMI) which could be identified as Islamic fundamentalism groups in Indonesia. The mainspring of the emergence of FPI and MMI was as the response (read: fear) to foreign forces that threatened and made Muslims suffered for a long time. The forms of movements and actions of FPI and MMI were so organized and used the spirit of the masses to respond to actual problems in the community that were sometimes missed by the authorities. As well as the interpretation of the concept of amar ma'ruf nahi munkar was promoted by FPI and the affirmation of MMI related to the prohibition on the use of logical reasoning in text interpretation. Those facts made these two groups legitimate as fundamentalism groups within the framework of Karen Armstong's analysis. Salah satu perkembangan pada akhir abad kedua puluh adalah munculnya di setiap tradisi agama sebuah kesalehan militan yang secara populer disebut “fundamentalisme”. Istilah ini juga dipakai untuk menunjukkan sebuah gerakan baru dalam kebangkitan Islam. Karen Armstrong membuat tiga karakteristik gerakan fundamentalisme, termasuk di dalamnya fundamentalisme Islam. Pertama, ideologi dan teologi gerakan ini berakar dari ketakutan. Kedua, gerakan-gerakan ini bukanlah sebuah hal kuno yang datang dari masa lampau, mereka adalah gerakan modern, inovatif dan memodernkan. Ketiga, kelompok fundamentalisme memiliki pemahaman agama secara tekstual. Perspektif Armstrong tentang fundamentalisme Islam ini berimplikasi pada Front Pembela Islam (FPI) dan Majelis Mujahidin Indonesia (MMI) yang dapat diidentifikasi sebagai kelompok fundamentalisme Islam di Indonesia. Raison d’etre FPI dan MMI yang hadir sebagai respon (baca: ketakutan) atas kekuatan-kekuatan asing yang mengancam dan membuat umat Islam mengalami penderitaan panjang; bentuk pergerakan dan aksi FPI dan MMI yang  begitu terorganisir dan menggunakan semangat massa untuk merespon permasalahan-permasalahan aktual di masyarakat yang terkadang luput oleh aparat; serta penafsiran konsep amar ma’ruf nahi munkar yang diusung oleh FPI dan penegasan MMI terkait larangan penggunaan nalar dalam interpretasi teks, membuat kedua kelompok ini sah sebagai kelompok fundamentalisme dalam kerangka analisis Karen Armstong.